Analisis Peran Struktur Signifikasi dan Dominasi dalam Peningkatan Partisipasi Pendidikan Anak Usia Dini - Julfadlina, Chairunnisa (UNIB Press, 2025)
The participation of children in early childhood education (PAUD) schools, measured by the PAUD Participation Rate (APK PAUD) in Indonesia, remains very low, ranging from 35 to 40 percent. Data released by BPS shows that over eight years, from 2015 to 2023, the APK PAUD in Indonesia has only increased by about one percent. This study analyzes the APK PAUD achievements by province and examines the relationship between signification structure and domination structure with APK PAUD using Anthony Giddens' structuration theory to see how agency is influenced by these structures in improving APK PAUD. A quantitative approach with secondary data is used in this research, and the unit of analysis is each province in Indonesia. Due to the type and distribution of data, the Spearman correlation test was chosen to examine the relationship between structure and agency. The results indicate that the signification structure, which consists of parental education and family harmony, as well as the economic conditions from the domination structure, do not have a relationship with APK PAUD. In contrast, two variables from the domination structure, which include the availability of school facilities and access to schools, are related to APK PAUD. The availability of school facilities has a weak and positive relationship with APK PAUD, while access to schools has a weak and negative relationship with APK PAUD.